Adsorption of Arsenate from Aqueous Solution onto Modified Vietnamese Bentonite - Nguyen Le My Linh; Duc Hoang Van; Tran Duong; Mai Xuan Tinh; Dinh Quang Khieu (Advances in Materials Science and Engineering)
In this study, pillared layered clays were prepared by modifying Vietnamese bentonite with polymeric Al and Fe. The obtained materials were characteristic of X-ray diffraction analysis, thermal analysis, and nitrogen adsorption/desorption isotherms. The results indicated that hydroxy-aluminum ([Al13O4(OH)24(H2O)12]7+) and poly-hydroxyl-Fe or polyoxo-Fe cations were intercalated into layers of clay, resulting in an increase of d001 values and of the specific surface areas compared with those of initial bentonite. Modified bentonites were employed to adsorb As(V) from aqueous solution. The adsorption of As(V) was strongly dependent on solution pH, and the maximum adsorption of modified bentonites was obtained in the pH 3.0 for Fe-bentonite and the pH 4.0 for Al-bentonite. The equilibrium adsorption study showed that the data were well fit by the Langmuir isotherm model. The maximum monolayer adsorption capacity of As(V) at 30°C derived from the Langmuir equation was 35.71 mg/g for Al-bentonite and 18.98 mg/g for Fe-bentonite. Adsorption kinetics, thermodynamics, and reusability of modified bentonites have been addressed.